2020
DOI: 10.3389/fmicb.2020.01353
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction and Characterization of Cationic Arginine-Rich Plant Antimicrobial Peptide SM-985 From Teosinte (Zea mays ssp. mexicana)

Abstract: Antimicrobial peptides (AMPs) are effective against different plant pathogens and newly considered as part of plant defense systems. From prokaryotes to eukaryotes, AMPs can exist in all forms of life. SM-985 is a cationic AMP (CAMP) isolated from the cDNA library of Mexican teosinte (Zea mays ssp. mexicana). A computational prediction server running with different algorithms was used to screen the teosinte cDNA library for AMPs, and the SM-985 peptide was predicted as an AMP with high probability prediction v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…Therefore, there is a distinct difference in the effectiveness of ZM-804 peptide on both bacterial groups, whereas Gram-negative bacteria are more sensitive than Gram-positive bacteria. ZM-804 agrees with the SM-985 peptide [ 45 ] in preference for Gram-negative bacteria, although they have no similar composition. Moreover, the MICs and MBCs of the ZM-804 are similar and close to previous studies on other AMPs such as NCR peptides [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, there is a distinct difference in the effectiveness of ZM-804 peptide on both bacterial groups, whereas Gram-negative bacteria are more sensitive than Gram-positive bacteria. ZM-804 agrees with the SM-985 peptide [ 45 ] in preference for Gram-negative bacteria, although they have no similar composition. Moreover, the MICs and MBCs of the ZM-804 are similar and close to previous studies on other AMPs such as NCR peptides [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…The activity of peptide NCR035 decreased after being labeled by FITC, and it was measured using PI uptake [ 55 ]. However, the FITC tag did not affect the antimicrobial activity of the SM-985 peptide [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent days, the AMPs are considered as potent alternatives to current chemical antibiotics for treatment of disease-resistant infections. Broad spectrum antimicrobial activity, greater efficacy at lowconcentration, higher specificity toward prokaryotic cells, low propensity for developing resistance and low relative cytotoxicity are the key attributes for considering AMPs in antimicrobial and therapeutic applications (Qutb et al, 2020;Sinha & Shukla, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have shown that antimicrobial peptides (AMPs) such as AtR472 derived from Aegilops tauschii Cosson , the cationic antimicrobial gene HCAP-18 expressed in Chinese cabbage, and peptide SM-985 from Teosinte ( Zea mays ssp. mexicana) have significant inhibitory effects on many plant pathogenic bacteria [ 8 , 9 , 10 ]. Besides, antimicrobial peptides have also been used in many fields because of their excellent bacteriostatic effects [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%